PROCEDURES FOR MANAGING INCOMING AND OUTGOING GOODS AT THE OUTLET KOPI GAYO DEPOK - Muhammad Adi Nugraha; Reni Naisya Putri; Subhan Faqih Aminullah (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
Inventory management at the Outlet Kopi Gayo recording incoming and outgoing goods requires good supervision, monitoring the use of raw materials, and the preparation of inventory reports must be carried out carefully. If the recording process is not done properly, there can be a discrepancy between the amount of inventory recorded and the actual amount of inventory. This study aims to determine the procedure for managing incoming and outgoing goods at the Outlet Kopi Gayo. The research method used is a descriptive method with qualitative approach through observation and interviews on inventory management activities. The results of the study show that the procedure for managing incoming goods includes the process of receiving, inspecting, recording, and storing goods, while the management of outgoing goods is carried out through the process of requesting, spending, recording, and updating stock data. The implementation of proper procedures will help in ensuring the availability of raw materials, improving the accuracy of inventory data, and supporting the smooth operation of the Outlet Kopi Gayo.